Modelling of plasma formation during nanosecond laser ablation - Mościcki, T.; Hoffman, J.; Szymański, Z. (Archives of Mechanics, 2011)
The interaction of laser beam with a target and next with the evaporated material is studied theoretically. In the case of a nanosecond laser pulse with 1064 nm wavelength, the ablation is thermal and therefore the interaction of the laser beam with a target is studied with the use of thermal model. The model which describes both the target heating, formation of the plasma and its expansion consists of equations of conservation of mass, momentum and energy and is solved with the use of Fluent software package. The calculations show a sharp increase of the plume temperature and pressure after plasma formation and following it, a considerable increase of the velocity of plasma plume. Maximum plasma pressure of 2 ×108 Pa, temperature of 61 500 K and front velocity of 3.8 × 104 m · s−1 have been found. The results show that the Mie absorption cannot be neglected in the phase of plasma formation. The shape of the plume and plasma front velocity obtained from the model are close to that observed in the experiment carried out in similar conditions.